2017
DOI: 10.5296/ije.v9i1.10915
|View full text |Cite
|
Sign up to set email alerts
|

Elementary School Teachers' Attitude towards Including Students with Special Educational Needs into Regular Public Schools in Saudi Arabia

Abstract: The inclusion of students with special educational needs (SEN) into the regular educational system is a major concern. Hence, in the present study, the reactions of 100 qualified reqular elementary school teachers were evaluated to explore their opinions on the inclusion of students with SEN in the mainstream schools within Saudi Arabia. Moreover, these opinions were scrutinized based on certain criteria of the teachers including gender, educational level, teaching experience, knowledge and awareness about SEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With an area of 865 000 square miles the KSA covers 80% of the Arabian Peninsula (Abed & Alrawajfh, 2017). Islam is the official religion and covers all aspects of people's lives.…”
Section: Introductionmentioning
confidence: 99%
“…With an area of 865 000 square miles the KSA covers 80% of the Arabian Peninsula (Abed & Alrawajfh, 2017). Islam is the official religion and covers all aspects of people's lives.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant finding was that there was no moderating effect of gender in this relationship. In fact, previous research conducted in the Saudi context (Abed & Alrawajfh, 2017;Al-Ahmadi, 2009;Alharthi & Evans, 2017;Alqahtani, 2017) has shown that educators can hold positive or negative beliefs, but no differences in their beliefs according to gender were revealed. Therefore, no studies have been found that have examined this specific relationship in the Saudi context.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, some other studies have examined the role and effect of gender on beliefs rather than the moderation effect of gender on a specific relationship related to educators' beliefs. Most of these studies have found significant differences between females and males with respect to their beliefs about inclusion (Abed & Alrawajfh, 2017;Al-Abduljabbar, 1994;Al-Ahmadi, 2009;Alqahtani, 2017;Rakap & Louise, 2010). On the other hand, there is also evidence that the gender of general educators has no effect on their beliefs (Alharthi & Evans, 2017;Chiner & Cardona, 2013;Cornoldi et al, 2018;Monsen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation